The Role of Bhabinkamtibmas on Kampung Tangguh Jaya Program in Reducing Violent Theft Crime During The Covid-19 Pandemic Period in The Legal Area of The Depok Metro Police - Filiari Notari (Advances in Police Science Research Journal, 2021)
With the increasing number of violent theft crimes during the COVID-19 pandemic, the role of Bhabinkamtibmas in the jurisdiction of the Depok Metro Police, which is concentrated in the “Kampung Tangguh Jaya” program, is in question. With the fact that during the COVID-19 pandemic, large-scale social restrictions have been implemented, which means that all activities in the community tend to be reduced. In this study, researchers want to know and analyze the role and factors that hinder the role of Bhabinkamtibmas in preventing criminal acts of theft with violence in the jurisdiction of the Depok Metro Police. Which researchers make the role of Bhabinkamtibmas as the main variable in this study. To answer the problems that occur in the jurisdiction of the Depok Metro Police, the researchers used several theories as analytical tools in this study. In this study, the theory used to thoroughly explore the existing problems is the role theory by Soerjono Soekanto (2002: 243) and the theory of management elements by G.R.Terry (In Usman Effendy: 2014). The findings that the researchers got during this research are that in the "Kampung Tangguh Jaya" program there is no clear budget where Bhabinkamtibmas operational activities continue to use the daily budget of Bhabinkamtibmas, in addition to the wide area of ​​Depok City and the lack of Bhabinkamtibmas personnel are also the main factors that later researchers will analyze more deeply in this study.